Perdagangan Internasional dan Restrukturisasi Industri TPT di Indonesia - Asdi Aulia (Business Administration Department - Universitas Katolik Parahyangan, 2008)
Considering that the Implementation of International Trade can be used to improvethe citizen welfare level, the governments from several countries formed WTO. Incontrast, there are a lot of problems caused by the different conditions among thecountries. Because of the regulation implemented to protect domestic products fromforeign product by developed countries, developing countries lose its competitiveadvantages. Thus developing countries, especially Indonesia, must try to increase itsbargaining power through WTO. To support this program, public accountant mustaudit government’s programs that have been disturbed by moral hazard during thelast period.Keywords: International Trade, WTO, Competitive Advantage, Regulation